2015
DOI: 10.5194/nhess-15-2461-2015
|View full text |Cite
|
Sign up to set email alerts
|

Detailed and large-scale cost/benefit analyses of landslide prevention vs. post-event actions

Abstract: Abstract. The main aim of this paper is to test economic benefits of landslide prevention measures vs. post-event emergency actions. To this end, detailed-and large-scale analyses were performed in a training area located in the northeastern Italian pre-Alps that was hit by an exceptional rainfall event occurred in November 2010. On the detailed scale, a landslide reactivated after 2010 event was investigated. Numerical modeling demonstrated that remedial works carried out after the landslide -water-removal in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The analysis of the costs also facilitated the consciousness of the economic sustainability of the considered soil bioengineering techniques in developing countries ( Petrone and Preti, 2010 ). Salbego et al (2015) performed CBA to analyse whether the drainage trenches which promote slope stability by reducing water table could be an economically feasible solution to prevent landslides caused by heavy precipitation in Vicenta province, northeast Italy. The study estimated that the landslides that occurred in 2010 incurred remediation costs of US$367.4 million and infrastructure and building losses of US$1.22 billion.…”
Section: Economic Evaluation Of Nbsmentioning
confidence: 99%
“…The analysis of the costs also facilitated the consciousness of the economic sustainability of the considered soil bioengineering techniques in developing countries ( Petrone and Preti, 2010 ). Salbego et al (2015) performed CBA to analyse whether the drainage trenches which promote slope stability by reducing water table could be an economically feasible solution to prevent landslides caused by heavy precipitation in Vicenta province, northeast Italy. The study estimated that the landslides that occurred in 2010 incurred remediation costs of US$367.4 million and infrastructure and building losses of US$1.22 billion.…”
Section: Economic Evaluation Of Nbsmentioning
confidence: 99%
“…A detailed numerical model found that incorporating a drainage trench (aiming to reduce the water table, therefore slope instability) prior to 2010 would have been effective in preventing the landslide. BCA showed that compared to €57,000 in remediation costs, installing a drainage channel and maintaining it over 20 years would have saved 30% of the remediation cost, leading to a benefit of €17,000 (Salbego, et al, 2015b).…”
Section: Box 22 Economics Of Prevention Versus Response For Landslides In Italymentioning
confidence: 99%
“…44 This fact modified the length between streams, which in turn varied the susceptibility to erosion and hillslope landslides. 73 As discussed by Salbego et al, 84 the use of preventive measures to protect road hillslopes from erosion is 30% more economical than applying passive or emergency measures a posteriori. Accordingly, the use of the branched drainage, instead of the traditional one, can be considered a preventive measure against erosion in road hillslopes.…”
mentioning
confidence: 99%